2019
DOI: 10.1515/hsz-2018-0469
|View full text |Cite
|
Sign up to set email alerts
|

Tripterine inhibits proliferation, migration and invasion of breast cancer MDA-MB-231 cells by up-regulating microRNA-15a

Abstract: Breast cancer is the most commonly diagnosed cancer in women worldwide. Tripterine is an important active component isolated from Triperygium wilfordii Hook F. This study investigated the effects of tripterine on breast cancer cell proliferation, migration, invasion and apoptosis, as well as microRNA-15a (miR-15a) expression. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was performed to measure the expression of miR-15a. Cell transfection was conducted to change the expression of miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Tripterine is a plant triterpene, which derives from the root of Thunder of God Vine, has been shown to possess antitumor activities. 5,6,[23][24][25] It has been reported that tripterine represses the growth and metastatic ability of gastric cancer cell MKN45 through down-regulating miRNA-21. 25 In addition, celastrol enhances ovarian cancer cell apoptosis through downregulating miRNA-21 and suppressing the PI3K/AKT/NF-κB signaling axis.…”
Section: Discussionmentioning
confidence: 99%
“…Tripterine is a plant triterpene, which derives from the root of Thunder of God Vine, has been shown to possess antitumor activities. 5,6,[23][24][25] It has been reported that tripterine represses the growth and metastatic ability of gastric cancer cell MKN45 through down-regulating miRNA-21. 25 In addition, celastrol enhances ovarian cancer cell apoptosis through downregulating miRNA-21 and suppressing the PI3K/AKT/NF-κB signaling axis.…”
Section: Discussionmentioning
confidence: 99%
“…The Western blot test showed that cyclin-dependent kinases (CDK1), a cell division associated protein, was lower expressed in si-UBE2C, but the apoptosis-associated factor, Bax, was higher expressed [ 6 ]. The protein level of C-PARP indicated that cell apoptosis was increased after the knockdown of UBE2C under 2 Gy irradiation ( Figure 3A ) [ 10 ]. And Bcl-2, a protein that suppresses apoptosis, was decreased in Si-UBE with 2 Gy irradiation group.…”
Section: Resultsmentioning
confidence: 99%
“…After relevant stimulation and/or treatment, cell apoptosis was tested via Annexin V-FITC/PI Apoptosis Detection Kit (Yeasen Biotechnology, Co., Ltd. Shanghai, China) [ 24 ]. A total of 3 × 10 4 H9c2 cells were cultivated in a 24-well plate for 24 h. Then, cells in each group were gathered, rinsed using PBS, and dyed with 5 μL Annexin V-FITC and 10 μL PI for 15 min protected from light.…”
Section: Methodsmentioning
confidence: 99%